Inflammatory factors, genetic variants, and predisposition for preterm birth. Issue 4 (28th May 2021) - Couceiro, Joana; Matos, Irina; Mendes, José João; Baptista, Pedro V.; Fernandes, Alexandra R.; Quintas, Alexandre
Abstract: Preterm birth is a major clinical and public health challenge, with a prevalence of 11% worldwide. It is the leading cause of death in children younger than 5 years old and represents 70% of neonatal deaths and 75% of neonatal morbidity. Despite the clinical and public health significance, this condition's etiology is still unclear, and most of the cases are spontaneous. There are several known preterm birth risk factors, including inflammatory diseases and the genetic background, although the underlying molecular mechanisms are far from understood. The present review highlights the research advances on the association between inflammatory‐related genes and the increased risk for preterm delivery. The most associated genetic variants are the TNFα rs1800629, the IL1α rs17561, and the IL1RN rs2234663. Moreover, many of the genes discussed in this review are also implicated in pathologies involving inflammatory or autoimmune systems, such as periodontal disease, bowel inflammatory disease, and autoimmune rheumatic diseases. This review presents evidence suggesting a common genetic background to preterm birth, autoimmune and inflammatory diseases susceptibility. Abstract :